Reports of Conferences, Institutes and Seminars. Issue 4 (2nd October 2018) - McAllister, Courtney; Seymour-Green, Marie; Mason, Kathie; Buck, Tina Herman; Wilkerson, Tami; Rubel, Dejah; Rogers, Kristin; Keller, Shannon; DiVittorio, Katy; Green, Jen; Kazmierczak, Anita; Fischer, Rachel K.; et al.
Abstract: This quarter's column offers several reports from the Electronic Resources & Libraries Conference held in Austin, Texas, on March 4–7, as well as coverage of sessions from the American Library Association Annual Conference, which took place in New Orleans, Louisiana, June 21–26. A handful of reports were also collected from the Library Publishing Forum in Minneapolis, Minnesota, on May 21–23; Ex Libris Users in North America (ELUNA) in Spokane, Washington, on May 1–4; Acquisitions Institute at Timberline Lodge in Oregon on May 19–21, and finally the NASIG conference in Atlanta, Georgia, on June 8–11. Topics covered include electronic resource tracking, trials, and troubleshooting; equity and diversity in acquisitions; technical services workflows; systems migrations; and library publishing pedagogy and open access.